Effectiveness of auditory distraction on the management of dental anxiety in patients undergoing tooth extraction at a tertiary care hospital in Islamabad - Sheze Haroon Qazi; Saba Masoud; Khadija Tariq; Minahil Khan; Reza Emrani; Javed Ashraf (Wiley, 2024)
Abstract Objectives The study aimed to assess the effectiveness of anxiety reduction protocol using auditory distraction in alleviating dental anxiety among patients undergoing tooth extraction. Materials and Methods A randomized controlled trial was conducted at the Oral Surgery Department at Islamabad Dental Hospital from July to December 2022, involving 50 patients scheduled for tooth extraction. Participants were randomly divided into two groups: an interventional group, exposed to auditory distraction, and a noninterventional group, without exposure to auditory distraction before the dental extraction. Dental anxiety was measured using the modified dental anxiety scale (MDAS) questionnaire, which scores anxiety levels on a range from 5 (not anxious) to 25 (extremely anxious). Anxiety levels were assessed in the waiting room and just before extraction, and the results were compared across both groups to evaluate the effectiveness of auditory distraction in reducing dental anxiety. Results The sample size of 50 was randomly and equally allocated to the interventional and noninterventional groups. The study population consisted of 28 (56%) female and 22 (44%) male participants. No significant difference was observed between the anxiety scores of interventional and noninterventional groups at baseline. A significant reduction in anxiety scores was observed in the intervention group during postintervention assessment, while no significant difference was seen in the noninterventional group's anxiety scores. Conclusions The study supports the efficacy of anxiety reduction protocol using auditory distraction as a practical tool for reducing dental anxiety among patients undergoing tooth extraction.